Magnesium Borate Synthesis by Microwave Energy: A New Method - Azmi Seyhun Kipcak; Emek Moroydor Derun; Sabriye Piskin (Journal of Chemistry)
Magnesium borates are one of the major groups of boron minerals that have important properties such as high heat and corrosion resistances and high coefficients of elasticity. In this study, magnesium borate minerals are synthesized using boric acid and magnesium oxide with a new method of microwave, and the synthesized minerals are characterized by various analysis techniques. The results show that pure, “magnesium borate hydrate” minerals are obtained at the end of various steps. The characterization of the products is determined with the techniques of X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), Raman Spectroscopy, and Scanning Electron Microscopy (SEM). Additionally, overall “magnesium borate hydrate” yields are calculated and found about 67% at 270 W, 8 minutes and 360 W, 3 minutes of reaction times, respectively.